(untitled) (The Research of Medical Science Review, 2024)
Background: Measles outbreaks occur continuously in Pakistan, causing severe mortality and morbidity in children. Proper immunization plays a vital role in the control of this disease.Objective: The objective of this study was to find out the immunization status, complications and outcome in children admitted with measlesMaterials and method: The current cross sectional study was carried out at women and children hospital Karak city from January 2023 to January 2024 after taking permission from the ethical committee of the institute. A total of 346 children of both sexes and different age groups were enrolled in this study. The research included kids who were hospitalized due to measles and related complications. Measles was identified in children with clinical symptoms. Participants' vaccination status was confirmed by checking their (EPI) card or contacting their parents if it was unavailable. In addition to a history and clinical examination, tests such as complete blood count, serum electrolytes, and X-ray of the chest were performed. All children were handled according to the hospital's usual protocol. Data was entered into MS Excel sheet and analyzed through SPSS version 23.Results: Over all 346 children presented with meals or its complication were examined. The most common age group was 1-3 years 200 (57.80%).The immunization status of the participants revealed that 56.3% were completely vaccinated against measles, 20.2% hadn't completed their vaccine, and 23.4% participants were not immunized. The most common complication associated with measles was pneumonia 150 (43.3%) , followed by Gastroenteritis 75 (21.6%) while in 91(26%) cases no complications were note. In regards of conclusion, the mortality rate was 3.4%. Pneumonia was the major cause of death. Most of individuals, 96% were discharged from Hospital within a week. Conclusion: It was concluded from this study that most measles patients were unvaccinated 23%. The most frequent complications were pneumonia and mortality rate was 3.4%. Complications were predominantly seen in unvaccinated children, underscoring the essential role of vaccination in mitigating measles-related morbidity and mortality.